EKSISTENSI PERMAINAN TRADISIONAL DI TENGAH DETERMINASI TEKNOLOGI DI KELURAHAN WANDUDOPI, KECAMATAN BARUGA KOTA KENDARI - Lestariwati, Lestariwati; Sudu, La; Magara, Irma; Suryati, Nurmin (Seshiski: Southeast Journal of Language and Literary Studies, 2021)
Determination of information technology is felt by all levels of society including the people in Kendari. On average, every child in the city of Kendari can already use a gadget or smartphone and most of them have it. Other devices that are also used to play games are computers and playstations with more sophisticated hardware specifications. Consequently, traditional games such as permainan bentengan. Petak umpet (hide and seek), bola bekel, gundu and gobak sodor increasingly marginalized. However, a different scene occurred in one of the neighborhoods in the Wandudopi village, Kendari City, children seemed play traditional games every time they get ready. In groups, they invite each other and negotiate to determine what game they will play. Therefore, this research was carried out with the aim of seeing how the existence of traditional games in the midst of the determination of information technology in the children of Wandudopi Village, Baruga District, Kendari City. To analyze it, it takes several concepts related to traditional games and information technology as well as several other social concepts that support this research. The method used is descriptive qualitative method in which data collection is done by means of documentation, interviews and observations. Then the data that has been collected will be analyzed with the concept as mentioned above. The results of this study indicated that, first, the types of traditional games that are often played by the children of Wundudopi village are ase, cuke, rubber jump (lompat tali), kasede-sede, kalego and bamboo shoots. Second, the factors that cause this game to exist in the midst of the determination of information technology are the approval of parents, habits and the existence of facilities from local residents.